Literature Across Borders: The Pilot Year Part 1: The Staff - Alexia Casale-Katzman; Meghaa Gupta; Alexander Robert Phillips (Leaf Journal)
This piece outlines the conceptualisation, planning, delivery and staff reflections on the culmination of the pilot year of the ‘Literature across Borders’ project, a collaborative endeavour between Ashoka University (India) and Bath Spa University (UK), facilitated by the Green Literature Festival (India). This piece accompanies a partner article (see this issue) exploring the reflections of eight of the pilot year student participants.